Therapeutic potential of traditional Chinese medicine in diabetic cardiomyopathy: a review - Li, Wencan; Liu, Xiang; Liu, Zheng; Xing, Qichang; Liu, Renzhu; Wu, Qinxuan; Zhang, Jiani (Frontiers in Endocrinology, 2025)
Diabetic cardiomyopathy (DCM) is a common cardiovascular complication that could lead to changes in cardiac structure and function. It is one of the leading causes of death in diabetic patients. Due to the complex pathogenesis of DCM, there is currently no specific drug or prophylactic agent to treat DCM, so there is an urgent need to identify new therapeutic agents or complementary and alternative therapies for DCM. Although Traditional Chinese medicine (TCM) has some limitations, it has the unique advantages of multi-level, multi-target and few side effects, which could effectively deal with the complex pathological mechanism of DCM. Growing evidence suggests that inflammation, oxidative stress, myocardial fibrosis and autophagy are the main pathological mechanisms of DCM. This study will shed light on the prospects of TCM treatment of DCM from the above perspective in order to provide more ideas and evidence for the clinical use of TCM for the prevention and treatment of DCM.